Lymphocytes Contribute to the Pathophysiology of Neonatal Brain Injury - Nazmi, Arshed; Albertsson, Anna-Maj; Rocha-Ferreira, Eridan; Zhang, Xiaoli; Vontell, Regina; Zelco, Aura; Rutherford, Mary; Zhu, Changlian; Nilsson, Gisela; Mallard, Carina; Hagberg, Henrik; Lai, Jacqueline C. Y.; et al. (Frontiers in Neurology, 2018)
Background Periventricular leukomalacia (PVL) is the most common form of preterm brain injury affecting the cerebral white matter. This type of injury involves a multiphase process and is induced by many factors, including hypoxia–ischemia (HI) and infection. Previous studies have suggested that lymphocytes play a significant role in the pathogenesis of brain injury, and the aim of this study was to determine the contribution of lymphocyte subsets to preterm brain injury. Methods Immunohistochemistry on brain sections from neonatal mice was performed to evaluate the extent of brain injury in wild-type and T cell and B cell-deficient neonatal mice (Rag1−/− mice) using a mouse model of HI-induced preterm brain injury. Flow cytometry was performed to determine the presence of different types of immune cells in mouse brains following HI. In addition, immunostaining for CD3 T cells and CD20 B cells was performed on postmortem preterm human infant brains with PVL. Results Mature lymphocyte-deficient Rag1−/− mice showed protection from white matter loss compared to wild type mice as indicated by myelin basic protein immunostaining of mouse brains. CD3+ T cells and CD20+ B cells were observed in the postmortem preterm infant brains with PVL. Flow cytometry analysis of mouse brains after HI-induced injury showed increased frequency of CD3+ T, αβT and B cells at 7 days after HI in the ipsilateral (injured) hemisphere compared to the contralateral (control, uninjured) hemisphere. Conclusion Lymphocytes were found in the injured brain after injury in both mice and humans, and lack of mature lymphocytes protected neonatal mice from HI-induced brain white matter injury. This finding provides insight into the pathology of perinatal brain injury and suggests new avenues for the development of therapeutic strategies.